Penentuan Status Mutu Air Dan Status Trofik Embung Ciseupan Kota Cimahi - Eka Wardhani; Virgy Vania Gary Apsari (Fakultas Teknik, 2023)
The Cimahi City has experienced a decrease in the quality of raw water caused by flooding in several places, especially during the rainy season, therefore it is necessary to anticipate this by constructing infiltration wells, ponds, or lakes. Cimahi City has 5 lakes, one of which is the Ciseupan Lake. This lake can be one of the options for raw water sources in Cimahi City. Based on this, it is necessary to identify the water quality and trophic status of the lake so that it can be utilized optimally by local residents. This research aims to describe the status of water quality and trophic status of the Ciseupan Lake by analyzing the parameters of pollutant sources. The method for determining the status of water quality is the Pollution Index based on Decree of the Ministry of Environment Number 115 of 2002 concerning “Pedoman Penentuan Status Mutu Air”. Quality status can be determined according to the pollutant index classification, the greater the value, then the worse the water quality. The method for determining trophic status uses the UNEP-ILEC method. Based on the results of calculating the water quality status, the pollutant index value at the Ciseupan Embung in 2021 is 9.5 while in 2022 it is 8.9 which according to Minister of Environment Decree Number 115 of 2003, in both years the water quality status of the lake was included in the moderately polluted category. The trophic status of the Ciseupan Lake is classified as hypertrophic, this indicates that the lake water has been heavily polluted by nutrients.